Study Of The Amount Of Chloroplast Pigment In The Leaves Of The Soy Collection Samples Grown As A Repeated Crop In The Conditions Of The Kashkadarya Region - Mavlonova G.D. (Euro Asian Journal Publishing, 2024)
This article presents the results of the analysis of the amount of chlorophyll "a", chlorophyll "b" and total chlorophyll in plant leaves from physiological indicators in the collection samples of soybean grown as a repeated crop in the conditions of Kashkadarya region during the flowering and podding periods. In the conditions of the Kashkadarya region, an increase in the amount of chlorophyll "a", chlorophyll "b" and total carotenoids was found in some soybean collection samples, and in some, a decrease.
Keywords: shade; collection; sign; flowering